Hydrogen peroxide treatment and its impacts on Lepeophtheirus salmonis originating from the Bay of Fundy, Canada. Issue 6 (4th November 2020) - VanIderstine, Carter R.; Poley, Jordan D.; Whyte, Shona K.; Purcell, Sara L.; Fast, Mark D.
Abstract: Hydrogen peroxide (H2 O2 ) is used to treat sea lice infections of farmed salmonids in the Atlantic and Pacific Oceans and issues with resistance to this treatment, and others are a major threat to the sustainability of the industry. The objectives of this study were to determine how H2 O2 exposure affects survival and antioxidant‐related gene expression in salmon lice ( Lepeophtheirus salmonis ) collected from the Bay of Fundy, New Brunswick. The maximum recommended dose of H2 O2 is 1, 800 mg/L, while the EC50 values (with 95% CI) for the population tested were 1, 486 (457, 2, 515) mg/L for males and 2, 126 (984, 3, 268) mg/L for females. Neither temperature nor pretreatment with emamectin benzoate (EMB) impacted survival after H2 O2 exposure. RT‐qPCR was performed on pre‐adult sea lice exposed to H2 O2 and showed that four genes classically involved in the response to oxidative stress were unchanged between treated and control groups. Seven genes were found to be significantly upregulated in males and one in females. This is the first report on the efficacy and molecular responses of Atlantic Canada sea lice to H2 O2 treatment.